Ferroelectric Nanogap‐Based Steep‐Slope Ambipolar Transistor (Small 48/2022). Issue 48 (1st December 2022) - Guan, Yaodong; Guo, Zhe; You, Long
Abstract : Steep‐Slope Devices In article number 2203017, Long You and co‐workers demonstrate a steep‐slope ambipolar transistor based on switchable ferroelectric nanogap with excellent performance, such as low subthreshold swing and high steep‐slope current densities, which has potential as a type of emerging steep‐slope device in the era of hyper Moore's law.